Chewing patterns in horses during the intake of variable quantities of two pelleted compound feeds differing in their physical characteristics only. (August 2019) - Bochnia, Mandy; Goetz, Franziska; Wensch-Dorendorf, Monika; Koelln, Mareike; Zeyner, Annette
Abstract: Pelleted feeds (PF) are popular in horse nutrition because of high palatability and improved feeding hygiene, but ingestion is faster for PF than for cereals or muesli feed. The aim of the study was to evaluate whether variable amounts of two PFs produced with different physical properties from the same batch of feed can affect feed intake patterns in horses. Chewing patterns were measured in six warmblood mares (519 ± 36.3 kg) on two PFs (small-sized PF1: ø 5 mm, length 21.9 ± 4.97 mm, large-sized PF2: edge length 15.6 ± 0.14 × 15.6 ± 0.08 mm, length 54.4 ± 9.59 mm) in three different amounts (1.0, 1.5, 2.0 kg) once per day additional to hay. PF 2 was ingested faster than PF1 for the meal size 1.0 kg, but PF 1 was ingested more rapidly with a reduced chewing intensity if the offered meal size increased. The ingestion of PF 2 tendentially elevated the chewing intensity at higher meal sizes. An additional, but inverted meal size effect compared to 1.0 kg, was observed for 1.5 kg, where PF 1 was ingested at a higher speed combined with a lower chewing intensity compared to PF 2. Independent from the offered amount, PF 2 induced a markedly increased saliva production combined with a higher daily water intake. Larger-sized pellets seem to intensify the chewing process and decelerate the ingestion time if the meal size becomes larger. Highlights: The present study suggest that chewing patterns in horses fed pelleted diets are affected by the physical characteristics hardness degree (HD) seems to be a predictor for saliva production and an intensified chewing process the offered meal size Larger-sized pellets with a higher HD might intensify the chewing process and decrease feed intake time in min kg −1 dm −1 . Last-mentioned can be extended even though the meal size exceeded. Interactions between pellet's physical properties and meal size can be beneficial for feeding practice and dental health.